Efektivitas Inovasi Program Smart Kampung Di Desa Ketapang Kabupaten Banyuwangi - Anisa Ana Fitrianti; Switsa Cellindita; Kayla Pramnesti (Journal of Governance Innovation, 2021)
This research aims to describe the effectiveness of e-goverment in the village of Ketapang District Kalipuro, Banyuwangi regency that implements the concept of Smart Kampung initiated by Banyuwangi Regency Government. The research used methods of literature study by analyzing the results of previous research with a variety of written sources of archives, books, articles, and journals with several documents relevant to the problems studied. The results of this research show the effectiveness of Smart Kampung program goes well. It can be seen from the input and output factors proposed in the compatibility theory proposed by Ali Muhiddin (2009). With holding of training and mentoring regularly and providing scholarships to the village apparatus to continue the education in order to be a superior human resources. The Ketapang village government is also very utilizing the utmost technology by using hardware and software to support the implementation of Smart Kampung innovations. The obstacles that stand out in this case are the problem of Internet networking is crucial to organize the Smart Village Innovation program based on information technology. Penelitian ini bertujuan untuk mendeskripsikan efektivitas e-goverment di Desa Ketapang Kecamatan Kalipuro, Kabupaten Banyuwangi yang menerapkan konsep Smart Kampung yang digagas oleh Pemerintah Kabupaten Banyuwangi. Penelitian ini menggunakan metode studi literature dengan menganalisis hasil dari penelitian terdahulu dengan berbagai sumber tertulis berupa arsip, buku, artikel, dan jurnal dengan beberapa dokumen yang relevan dengan permasalahan yang akan dikaji. Hasil penelitian ini menunjukkan efektivitas program Smart Kampung berjalan dengan baik. Hal tersebut dapat dilihat dari faktor input dan output mengacu pada teori efektivitas yang dikemukakan oleh Ali Muhiddin (2009) . Diadakannya pelatihan dan pendampingan secara rutin serta memberikan beasiswa kepada aparatur desa untuk meneruskan pendidikan agar nanti dapat menjadi SDM yang unggul. Pemerintah Desa Ketapang juga sangat memanfaatkan tekhnologi secara maksimal dengan menggunakan hardware dan software untuk mendukung pelaksanaan inovasi Smart Kampung. Adapun hambatan yang menonjol dalam hal ini yakni, masalah jaringan internet merupakan hal yang krusial untuk menyelenggarakan program inovasi Smart Kampung yang berbasis tekhnologi informasi.